EISENSTEIN IRREDUCIBILITY CRITERION FOR MODULES - (:unkn) unknown (PUBL HOUSE BULGARIAN ACAD SCI, 2021)
In this article, we study factorial modules. Let M be a torsion free module over an integral domain R. We prove Gauss Lemma for modules and also we give Eisenstein irreducibility criterion for factorial modules. Furthermore, we give some applications of Eisenstein irreducibility criterion in R[X]-module M[X].
Keywords: Eisenstein irreducibility criterion; primality test; MILD GENERALIZATION; SCHONEMANN; DUMAS